Enable contrast version

# Tutor profile: Farhan K.

Inactive
Farhan K.
College Student willing to teach advanced subjects
Tutor Satisfaction Guarantee

## Questions

### Subject:Pre-Algebra

TutorMe
Question:

Solve the following problem using substitution (y-2)/3=2x -3x+2y=22

Inactive
Farhan K.

To solve this problem, we need to isolate a variable and substitute that variable into the other equation to solve for the answer. Step 1: Isolate a variable- You can multiply both sides by 3 to cancel the 3 in the denominator, then add 2 to both sides to move the -2 from one side of the equation to the other (y-2)/3=2x = 3((y-2)/3)=3(2x) = y-2=6x = y=6x+2 Step 2. Substitute the value of y that you solved for into the other equation to calculate the value of x -3x+2y=22 = -3x+2(6x+2)=22 = -3x+12x+4=22 = 9x+4=22 = 9x=18 = x=2 Step 3. Plug the value of x back into one of the equations to find the value of y y=6x+2 = y=6(2)+2 = y=12+2 = y=14 Step 4. Check your work by plugging in both variables into an original equation and see if both sides of the equation are equal. (y-2)/3=2x = (14-2)/3=2(2) = 12/3=4 = 4=4 Congratulations! You have now learned how to solve equations using substitution!

### Subject:Basic Chemistry

TutorMe
Question:

What is the difference between acids and bases?

Inactive
Farhan K.

An acid is a solution that contains a large amount of hydrogen ions and a base contains a small amount of hydrogen ions. This means that when both are mixed together, the acid will donate hydrogen ions to the base. Therefore acids are often called "proton donators" and basses are often called "proton acceptor ".

### Subject:Algebra

TutorMe
Question:

Solve the following problem using substitution (y-2)/3=2x -3x+2y=22

Inactive
Farhan K.

To solve this problem, we need to isolate a variable and substitute that variable into the other equation to solve for the answer. Step 1: Isolate a variable- You can multiply both sides by 3 to cancel the 3 in the denominator, then add 2 to both sides to move the -2 from one side of the equation to the other (y-2)/3=2x = 3((y-2)/3)=3(2x) = y-2=6x = y=6x+2 Step 2. Substitute the value of y that you solved for into the other equation to calculate the value of x -3x+2y=22 = -3x+2(6x+2)=22 = -3x+12x+4=22 = 9x+4=22 = 9x=18 = x=2 Step 3. Plug the value of x back into one of the equations to find the value of y y=6x+2 = y=6(2)+2 = y=12+2 = y=14 Step 4. Check your work by plugging in both variables into an original equation and see if both sides of the equation are equal. (y-2)/3=2x = (14-2)/3=2(2) = 12/3=4 = 4=4 Congratulations! You have now learned how to solve equations using substitution!

## Contact tutor

Send a message explaining your
needs and Farhan will reply soon.
Contact Farhan